Cultivation of the gut bacterium Prevotella copri DSM 18205T using glucose and xylose as carbon sources. Issue 3 (27th June 2021) - Huang, Fang; Sardari, Roya R. R.; Jasilionis, Andrius; Böök, Olof; Öste, Rickard; Rascón, Ana; Heyman‐Lindén, Lovisa; Holst, Olle; Karlsson, Eva Nordberg
Abstract: Prevotella copri DSM18205 T is a human gut bacterium, suggested as a next‐generation probiotic. To utilize it as such, it is, however, necessary to grow the species in a reproducible manner. Prevotella copri has previously been reported to be highly sensitive to oxygen, and hence difficult to isolate and cultivate. This study presents successful batch cultivation strategies for viable strain inoculations and growth in both serum bottles and a stirred tank bioreactor (STR), without the use of an anaerobic chamber, as long as the cells were kept in the exponential growth phase. A low headspace volume in the STR was important to reach high cell density. P . copri utilized xylose cultivated in Peptone Yeast Xylose medium (PYX medium), resulting in a comparable growth rate and metabolite production as in Peptone Yeast Glucose medium (PYG medium) in batch cultivations at pH 7.2.Up to 5 g/L of the carbon source was consumed, leading to the production of succinic acid, acetic acid, and formic acid, and cell densities (OD620 nm ) in the range 6−7.5. The highest yield of produced succinic acid was 0.63 ± 0.05 g/g glucose in PYG medium cultivations and 0.88 ± 0.06 g/g xylose in PYX medium cultivations. Abstract : Successful batch cultivation strategies for reproducible growth of the anaerobe Prevotella copri DSM18205 T, in both serum bottles and stirred tank reactor, are presented. Critical inoculum conditions were revealed and confirmed viable strain transfer without the use of an anaerobic chamber. The study provides fundamental knowledge to enable future commercial production.